Partnership Strategy of Course and Training Institutions in Guaranteing the Quality of Education with the World of Work Industry: A Review - Susilowati, Rini (Jurnal Penelitian Pendidikan IPA, 2023)
The role of the Unna Course and Training Institute (LKP) is very necessary in obtaining competent skills to meet the needs of society, especially in the field of beauty. LKP Unna aims to be able to produce graduates who are competent, efficient, and able to compete in the Business World, Industry, and Work World (DUDIKA) in the field of beauty. This research method is a review method. Journal review method by comparing one journal with another journal in the sense of integrating the results of analysis of research journals based on the similarities and differences of each and then providing new conclusions. This research aims to create an effective strategy for LKP Unna to ensure the quality of graduates so they can compete in the labor market. The government implements various policies so that the quality of Course and Training Institutions (LKP) is guaranteed, including LKP must have; NPSN; Accredited; Have Institutional Performance Assessment and process quality assurance, Course and Training Institutions ( LKP) must implement curriculum standards using: the Indonesian National Framework (KKNI), Graduate Competency Standards (SKL), and Project Based Learning (PBL) based curriculum and translated into Learning Implementation Plans (RPP) and Teaching Materials. The partnership strategy used is to be equal and in line with the needs of the world of work industry, the aim of which is to penetrate the labor market both nationally and internationally. In the industrial world of work, several aspects can collaborate including curriculum, instructors, marketing, mentoring, apprenticeships, and job placement of LKP graduates in related industrial worlds